Distribution of 14C-DDT and its metabolites in a model mudflat ecosystem - Abdullah, A.R.; Subramaniam, S.; Arshad, J.; Wong, K.Y. (Malaysian Journal of Science, 1999)
The distribution of 14C-DDT and its metabolites in a model mudflat ecosystem comprising water, sediment and cockles (Anadara granosa) was investigated for a period of 21 days under laboratory conditions. The rapid decrease in 14C-DDT concentration in water coincided with a corresponding increase in concentration of the chemical in sediment which reached a maximum of 84.4 % of the applied I4C activity at the end of the study period. The proportion of extractable residues in the sediment was also noted to increase gradually with time at the expanse of bound residues. The 14C activity in cockle tissue was relatively constant, averaging 19.8 % of the total applied activity. At the end of the 21-day study, 71 % of the residue in the tissue was bound. DDT was the major chemical identified in water, sediment and cockle tissues. Traces amounts of DDE and DDD were also detected in the later part of the study.